FMCW radar signal processing - Application on INDERA - Sediono, Wahju (2017)
At present, radar has become a standard system on all commercial vessels, and is widely used in the leisure maritime sector. Especially in the area with high dense vessel traffic, radar retains its primary role in collision avoidance. The use of radar as primary navigational aid as well as safety tool is still an essential part of safe watch-keeping.